Historic Building Information Modelling (HBIM): The Application of Digitalization in Conserving Negeri Sembilan Traditional Malay House - Siti Azira, Abd Rahim*; Noor Hayati, Ismail; Nurul Syala, Abd Latip; Nurulhuda, Ahamad; Mohd Amir Shazwan, Hashim; Farhana, Mohd Zaini; Sangeetha, Arjinan (INTI International University, 2022)
Rumah kampung, or Malay house, exemplifies the richness and insight of traditional buildings, sharing a home with people, and living in peace with nature. The typical Malay home is a building elevated on stilts high above the ground, covered with thatch roofs, encased with wooden walls, and pierced with windows and lattices in its most basic form. Due to the increasing interest in cultural heritage as a driving force of socio-economic development, many initiatives involving its preservation, conservation, restoration, and dissemination are undertaken throughout the globe. Conservation entails taking physical steps to preserve the fabric and elements of heritage buildings. It is a method of preventing deterioration from extending the life of buildings. According to the conservation concept, building conservation should maintain as much of the original building structure and fabric as feasible. Heritage buildings are now conserved based on historical and cultural considerations, and the cultural value of the architecture of historic buildings is slowly appreciated. The techniques, methods, and materials used to build and construct the buildings are the primary concern in conservation projects. This paper aims to investigate the current conservation process using the digitalization approach to document Negeri Sembilan Traditional Malay House. Data collection provides a literature review, whereby the current conservation process for cases in Malaysia and various countries will be reviewed. Content analysis was utilized to analyze the results. The findings of this paper provide helpful information regarding the potential development of digitalization based on the conservation process to be used further in the future traditional conservation building.